Budgeting in the Netherlands - Blöndal, Jón R.. (OECD Publishing, 2002)
The budget formulation process in the Netherlands operates in two very distinct phases. The first phase occurs when a new government takes power and it establishes its overall budgetary policy for its term of office. This is done in explicit terms, rather than being a general statement of intent. The second phase then occurs annually, as the government's overall budgetary policy is translated into operational terms for all of the government's various activities...
Keywords: Governance; Netherlands